« Crétins internationaux », « rancis de la Guerre froide » et autres suicidés - Claire Oger (Communication)
This article proposes a reading of the emergence of verbal violence — in the form of invectives — during the unfolding of polemics between intellectuals in the written press. Firstly, we will attempt to tease out the inflections on the road that leads gradually and almost insensitively from insult to injury, and we will show how this transformation is held together by an apparatus of putting the adversary into a particular scenario in the discourse. Finally, in light of this double pathway into the corpus, we will attempt to propose a few hypotheses and situate them in relation to concepts developed by other researchers.